Toward a dynamic capabilities’ diffusion model for international business headway of SMEs: Evidence from the metallurgic and metal-mechanic (MMI) sectors - Abrantes, B. F.; Preto, M. T.; António, N. (Review of International Business and Strategy, 2022)
Purpose: This paper aims to explore the characteristics of capability exchange within internationalizing small and medium enterprises (SMEs) of the Portuguese metallurgic and metal-mechanic sectors. Design/methodology/approach: Multiple case research instrumentalizes a (manifest) content analysis based upon qualitative data gathered from the interviewing of the strategic apex of four multinational enterprises, codified in the light of the well-known Weber protocol. Findings: The results uncover the existence of a multi-diffusional approach with a bi-directional regime of transferability, where reciprocal transference is non-simultaneous. Operational rigidities are asserted to be stifling the diffusion of capabilities across subsidiaries and hindering higher economies of learning. Research limitations/implications: The current paradigm of international capabilization of the sector requires substantial enhancements in its design for the benefit of the firm’s international competitiveness, growth and wealth. Originality/value: Organizational capabilities are a determinant of competitiveness. Hitherto, the phenomena of (capabilities) mobility and transferability are still acknowledged as a clear gap. This study opens, therefore, avenues on international capabilization in relation to the modeling and testing of global dynamic capabilities and its replicability across industries.